Improvement of solar cell efficiency and electrical energy of a photovoltaic-thermal system by using nanofluid - Marhama Jelita; Habibis Saleh (Penerbit Universiti Kebangsaan Malaysia, 2023)
This communication presents the finite element method (FEM) analysis of the conjugate heat transfer across the PV/T panel. The PV/T system has several layers i.e., PV cell layer, thermal paste layer, reservoir wall and reservoir flow channel filled with nanofluid. The heat transfer equations for all layers have been constructed according to the conjugate heat transfer equation. The continuity, momentum and energy equations are solved numerically by using the FEM technique. The effects of various dimensionless parameters are discussed by plotting velocity, temperature, electrical output and thermal efficiencies. The result indicates that the average cell temperature keeps decreased by increasing nanoparticle concentration. The narrower flow channel has greater power output at the relatively low concentration while the wider flow channel has greater power output at the relatively high concentration. Thermal performance increases by 11% for every 10% increasing in nanoparticle volume fraction.